2014
DOI: 10.1182/blood-2014-06-583021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical heterogeneity and predictors of outcome in primary autoimmune hemolytic anemia: a GIMEMA study of 308 patients

Abstract: Key Points• Mixed, atypical, and warm immunoglobulin G plus C AIHA (;30% of cases) more frequently have a severe onset (Hb #6 g/dL) and require multiple therapy lines.• Infections, particularly after splenectomy, acute renal failure, Evans syndrome, and multitreatment, were predictors of fatal outcome.The clinical outcome, response to treatment, and occurrence of acute complications were retrospectively investigated in 308 primary autoimmune hemolytic anemia (AIHA) cases and correlated with serological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
402
7
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 286 publications
(441 citation statements)
references
References 49 publications
22
402
7
10
Order By: Relevance
“…Additionally, we acknowledge that our patients' initial clinical presentation of AIHA may not correspond to their date of diagnosis in STRIDE, which can be typical for tertiary referral centers like Stanford. This may explain why we found that AIHA patients Austin Publishing Group Submit your Manuscript | www.austinpublishinggroup.com with thrombosis did not have more severe laboratory evidence of haemolysis at the time of their diagnosis at Stanford than those without thrombosis, in contrast to prior studies [19]. Being a tertiary center, Stanford's patient population is also likely to have more severe disease.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Additionally, we acknowledge that our patients' initial clinical presentation of AIHA may not correspond to their date of diagnosis in STRIDE, which can be typical for tertiary referral centers like Stanford. This may explain why we found that AIHA patients Austin Publishing Group Submit your Manuscript | www.austinpublishinggroup.com with thrombosis did not have more severe laboratory evidence of haemolysis at the time of their diagnosis at Stanford than those without thrombosis, in contrast to prior studies [19]. Being a tertiary center, Stanford's patient population is also likely to have more severe disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Prior studies have shown that thrombosis is correlated with low hemoglobin at the time of AIHA onset and laboratory evidence of haemolysis [19,20]. We did not find these to be the case for our AIHA cohort.…”
Section: Characterizing the Relationship Between Thrombosis And Haemocontrasting
confidence: 40%
See 3 more Smart Citations